Manajemen Pendidikan Ahklakul Karimah dalam Surat Al-Ahzab Ayat 21 - Murniyanto (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2022)
The focus of this study is the management of akhlakul karimah education in surah Al-ahzab verse 21 which is related to morals in a the Koran, then from the verses it is known what meaning is implied in it. The purpose of this study is to explain what is the meaning of morality in the Qur'an and how it is interpreted regarding morals in the modern era which is declining. This research is included in library research, namely collecting data through readings, books and literature that are relevant to the research title. then studied in depth and thoroughly from various aspects that can be explored. Growing education management ahlakkul karimah in surah Al-Ahzab verse 21. The results of the research in the letter Al-Ahzab verse 21 The figure of Rasulullah SAW is a barometer of life and a role model for humans. As the messenger of Allah SWT. Rasulullah SAW. successfully revived the message in himself and for those around him. The characteristics, attitudes and values ​​that he brought are a representation of the teachings of the Koran. This can be seen from his four characteristics which can be emulated for the current era of modernization; Shidiq, Amanah, Fatanah, Tabligh.